Novel Mutations in pncA Gene of Pyrazinamide Resistant Clinical Isolates of Mycobacterium tuberculosis - Kahbazi, Manijeh (Sci Pharm, 2018)
In clinical isolates of Mycobacterium tuberculosis (MTB), resistance to pyrazinamide occurs by mutations in any positions of the pncA gene (NC_000962.3) especially in nucleotides 359 and 374. In this study we examined the pncA gene sequence in clinical isolates of MTB. Genomic DNA of 33 clinical isolates of MTB was extracted by the Chelex100 method. The polymerase chain reactions (PCR) were performed using specific primers for amplification of 744 bp amplicon comprising the coding sequences (CDS) of the pncA gene. PCR products were sequenced by an automated sequencing Bioscience system. Additionally, semi Nested-allele specific (sNASP) and polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) methods were carried out for verification of probable mutations in nucleotides 359 and 374. Sequencing results showed that from 33 MTB clinical isolates, nine pyrazinamide-resistant isolates have mutations. Furthermore, no mutation was detected in 24 susceptible strains in the entire 561 bp of the pncA gene. Moreover, new mutations of G→A at position 3 of the pncA gene were identified in some of the resistant isolates. Results showed that the sNASP method could detect mutations in nucleotide 359 and 374 of the pncA gene, but the PCR-RFLP method by the SacII enzyme could not detect these mutations. In conclusion, the identification of new mutations in the pncA gene confirmed the probable occurrence of mutations in any nucleotides of the pncA gene sequence in resistant isolates of MTB.